การศึกษาเปรียบเทียบประชาธิปไตยตัวแทนและประชาธิปไตยทางเลือก ว่าด้วยธรรมชาติมนุษย์ - โชติสา ขาวสนิท (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this dissertation is to clarify and compare the ideas of "human nature" understood by representative and alternative democratic theorists. Regarding research methodology, the author takes close taxtual analysis in political philosophy. This dissertation proceeded on the hypothesis that representative democratic theorists place an emphasis on the dark side of human nature but alternative democratic theorists place an emphasis on the bright side of human nature. The findings of this dissertation confirms the hypothesis. The findings of this dissertation are as follows; 1. Representative democratic theorists believe that human beings are classified into two fixed groups, that are ignorant majorities and intelligent minorities. The former should have important roles in leading the country while the latter should follow the intelligent few. On the contrary, alternative democratic theorists thin that there are no fixed classes of leaders and followers. Anyone can develop one’s political abilities of the majorities more than representative democratic ones. 2. Representative democratic theorists think that human beings are rather unreliable but alternative democratic theorists think in a very different way. Alternative democratic theorists except Robert A. Dahl realize that power can corrupt human beings but it is up to individual mind to let power influence him like this or not. On the contrary, representative democratic theorists except John Stuart Mill and Halminton believe that anyone who possesses absolute power cannot control oneself. John Stuart Mill and Halminton think that few people can overcome their passions when they hold unchecked power.